Improving the Community Services through Electronic Management of East Pringsewu Subdistrict Administration - Tri, Susilowati; Sri, Hartati; Mardiyanto, .; Bimo Bagus, Prabowo, (INTI International University, 2024)
Every Government Institution cannot be separated from carrying out daily administrative activities. Manuscripts or recordings of documents or information, including text, images, and sound recordings, are called archives because archives are records of every activity carried out. Currently, the East Pringsewu sub-district office for filing letters and other activities still uses manual methods. The implementation of E-Government is expected to enable all service activities to the community to be carried out electronically, thereby simplifying policy and service functions. The data collection methods used in this writing are observation, documentation, interviews, and literature study. The SDLC (System Development Life Cycle) method is used in this research, namely a systematic approach to planning, designing, developing, testing, and maintaining software systems. Based on needs analysis, the system developed focuses on managing population data, archiving, and correspondence related to village authority. Before implementing the system, it is necessary to design the system. When designing a system, use the Unified Modeling Language (UML) approach using Use Case Diagrams, Activity Diagrams, and Class Diagrams. Use case diagrams to describe the interaction between users and the system being developed. This research uses the PHP programming language and Visual Studio Code as a text editor and MySQL DBMS. Applications can be used as a medium for implementing subdistrict or village development with information technology and supporting the progress of subdistricts or villages by Government recommendations in developing E-Government.